Pioneers in cell biology [ - Cregan, Elizabeth R. (Huntington Beach, California : Teacher Created Materials, 2008)
Anton van Leeuwenhoek was not educated in science, but he created the best microscopes of the 17th century. He made more than 400 microscopes and used them to study living organisms. British scientist Robert Hooke was the first scientist to observe cells and give them their name. Many scientists are still making discoveries in the areas of genetics and stem cell research
1. Anton van Leeuwenhoek -- 2. August Weismann -- 3. Joan Wright Goodman -- 4. Christiane Nusslein-Volhard -- 5. Developmental Biologist Rita Levi-Montalcini -- 6. Lab: cell mobile models.Volhard -- 6. Developmental Biologist Rita Levi-Montalcini -- 7. Lab: cell mobile models
Description based on print version record
Includes index
Keywords: Biologists -- Biography; Biologists -- Biography -- Juvenile literature